Pendampingan Penulisan Artikel Penelitian Tindakan Kelas di Sabu Raijua - Daud Saleh Luji; Ezra Tari; Adrian Wirya Syahputra; Jefrianus Taneo (Universitas Lancang Kuning, 2022)
The significance of classroom action research in improving the learning process and quality in the classroom and classroom action research for teacher career advancement in terms of rankings and suggested career paths. The aim is to help teachers understand the importance of writing. The method used is, first, the basic concept of classroom action research. Second, practice writing action research in the classroom. And a summary of the results. From the training results, it is known that after following the material, understanding and mastery of CAR increased compared to before. Teachers can understand the duties and responsibilities in writing activities in class. So the teacher can understand the importance of references in writing articles.